2020
DOI: 10.1177/0033354920968799
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging 31 Million Google Street View Images to Characterize Built Environments and Examine County Health Outcomes

Abstract: Objectives Built environments can affect health, but data in many geographic areas are limited. We used a big data source to create national indicators of neighborhood quality and assess their associations with health. Methods We leveraged computer vision and Google Street View images accessed from December 15, 2017, through July 17, 2018, to detect features of the built environment (presence of a crosswalk, non–single-family home, single-lane roads, and visible utility wires) for 2916 US counties. We used mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 43 publications
(73 reference statements)
1
17
0
Order By: Relevance
“…Uninsured patients were less likely to live in areas with green streets and non-single homes. In one of our previous studies, we found that greater county-level economic disadvantage was associated with a lower prevalence of non-single-family homes and visible wires at the county level after adjusting for violent crime rate, age, race/ethnicity, percentage of population not proficient in English, and ratio of population to primary care providers [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uninsured patients were less likely to live in areas with green streets and non-single homes. In one of our previous studies, we found that greater county-level economic disadvantage was associated with a lower prevalence of non-single-family homes and visible wires at the county level after adjusting for violent crime rate, age, race/ethnicity, percentage of population not proficient in English, and ratio of population to primary care providers [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is among the few studies examining GSV-derived predictors of individual-level outcomes, controlling for individual-level predisposing characteristics. Previous studies with GSV images have utilized ecological frameworks [ 48 ]: for instance, county-level built environment predictors of county health outcomes [ 49 ]. In partnership with one of the largest healthcare providers in Utah, in this study, we included close to one-third of the population in Utah.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of crowdsourced mapping services and geotagged imagery containing a wealth of visual information [e.g., Baidu Street View, Tencent Street View, and Google Street View (GSV)] provides a usable source of big data. Mapping services provide academics and researchers with an application programming interface (API) for extracting high-spatial resolution images of streets and communities to reflect a built environment as its residents see it ( 14 ). GSV is now available in many countries and cities around the world, becoming a scholarly tool for studying the built environment of cities because of its wide coverage and high accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…This approach typically requires mass downloading of Street View images in order to efficiently process the images on high-performance computational clusters. There have been notable successes in training machines to quantify trees and green space and to identify traffic control signs, crosswalks, single-lane roads, and utility wires in Street View panoramas [ 20 – 26 ]. Recent work has also used health data from surveys to train a generative adversarial networks (GAN) machine learning model to identify health-related features in Street View images [ 27 ].…”
Section: Introductionmentioning
confidence: 99%